Building foundations in English - Nor Hasni Mokhtar (Cengage Learning Asia, 2012)
Building foundations in English is designed to help elementary learners to build their confidence and enhance their proficiency in the English language. This book adopts an integrated skill-based approach and each chapter has a specific learning point with a variety of topics and interesting activities. This book focuses on the four language skills of reading, writing and speaking, while listening is indirectly integrated into the chapters. It also aims to equip students with dictionary skills, and perfect their grammar and pronunciation abilities. Building Foundations in English therefore can be used to help students use and apply basic grammar, write good sentences and paragraphs correctly and improve their general comprehension skills